Wawasan Al-Qur’an Tentang Metode Pendidikan - Zulfikar Ali Buto (JURNAL TARBIYAH, 2018)
The Qur'an is revealed to mankind, as a source of guidance, a source of inspiration and a source of knowledge of knowledge, one of which is related to education. al-Qur'an is one of the main sources of knowledge for Muslims who have a wide range that is always in accordance with the times. This article seeks to explore the Qur'anic insights about educational methods by seeking the terms in some verses of the Qur'an that can give meaning to the method of learning. Further explores and explains it by the thematic interpretation of the mufassrins. Based on the verses analyzed through thematic interpretation obtained ta'lim method, the method of wisdom, mau'izah, and so as in the letter An-Nahl verse 125.